Pendampingan Orang Tua dalam Menerapkan Pendidikan Akhlak Anak Usia Dini Berbasis Islam di Desa Joho, Kec. Pace, Kabupaten Nganjuk - Anik Indramawan; Leily Vidya Rahma; Agus Tohawi; Muhamad Ali Anwar; Mastur Mastur; Nur Fuad; Achmad Fauza Setyo Utomo (Eastasouth Journal of Effective Community Services, 2023)
This study explores the implementation of parental guidance in fostering Islamic-based moral education for early childhood in Joho Village, Pace District, Nganjuk Regency. The program emphasizes the active involvement of parents in collaboration with educators to instill core Islamic values such as honesty, empathy, and responsibility in young children. Using a qualitative approach, the research highlights the importance of synergistic relationships between families, schools, and the community known as the "Tripusat Pendidikan" (Three Centers of Education) to create a supportive environment for character development. The findings demonstrate that practical methods, including storytelling, habituation, and exemplary behavior, are effective in shaping children's moral character. The study also identifies key supporting factors, such as high parental motivation and community support, as well as challenges like varying educational backgrounds and time constraints among parents. Overall, the program successfully enhances parents' confidence and skills in moral education, and the collaborative approach ensures the sustainability of Islamic character formation in early childhood.